2018
DOI: 10.2147/opth.s115098
|View full text |Cite
|
Sign up to set email alerts
|

Patient and physician perspectives on the use of cyclosporine ophthalmic emulsion 0.05% for the management of chronic dry eye

Abstract: Dry eye disease (DED) is a multifactorial disease of the ocular surface and is one of the most common reasons for patients to visit an eye care provider. Cyclosporine A (CsA) is an immune modulating drug that was approved in the US for topical use in the treatment of DED in 2003, which led to a paradigm change in our understanding and treatment of DED, turning attention to control of inflammation for treatment. This review summarizes the literature to date regarding the impact of CsA on the treatment of DED. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 63 publications
2
13
0
Order By: Relevance
“…The significant differences in satisfaction scores between baseline and 1 and 2 months after treatment in group 3 are consistent with previous reports and are not unexpected because photophobia, burning, and pain are subjective symptoms and have a greater impact on satisfaction scores [ 12 , 27 ]. Corticosteroid supplementation has also been shown to be helpful in reducing ocular surface inflammation, as corticosteroids inhibit proinflammatory cytokines [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…The significant differences in satisfaction scores between baseline and 1 and 2 months after treatment in group 3 are consistent with previous reports and are not unexpected because photophobia, burning, and pain are subjective symptoms and have a greater impact on satisfaction scores [ 12 , 27 ]. Corticosteroid supplementation has also been shown to be helpful in reducing ocular surface inflammation, as corticosteroids inhibit proinflammatory cytokines [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…These include elevated intraocular pressure and induced glaucoma, cataract formation, delayed wound healing, and increased susceptibility to infection [57]. Furthermore, the most common reported side effect of CsA is ocular burning, reported in 17% of patients, and approximately 3% of patients stop the medication as a result of this side effect [7].…”
Section: Side Effectsmentioning
confidence: 99%
“…Ocular inflammation is considered as a major eye disorder and many reports demonstrated that topical administration of anti-inflammatory drugs, non-steroidal (NSAIDs) [1] and steroidal (SAIDs) [2], are effective in treating ocular surface and anterior segment inflammation, including pain and post-operative inflammation, seasonal allergic conjunctivitis [3,4], and age-related macular degeneration [5]. Furthermore, some immunosuppressive agents, such as ciclosporin A (CsA), demonstrated their efficiency in the treatment of keratitis associated with dry eye disease (DED) [6,7]. The major challenge in the therapeutic management of ocular inflammation is rapid treatment in order to reduce the risk of visual impairment while limiting side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Topical administration of ocular therapy is expected to avoid the side effects associated with systemic delivery of drugs such as CsA [9]. Reviews have found that most studies have demonstrated improvement in at least some symptoms of dry eye in patients treated with topical CsA [10, 11]. Following topical administration, CsA is expected to achieve effective drug concentrations in the immune response and inflammatory target areas [12].…”
Section: Main Textmentioning
confidence: 99%
“…All of the potential barriers to drug penetration from topical administration had a total drug loss of about 95% with the remainder encountering corneal and conjunctival epithelial barriers [14]. More frequent dosing may be used to improve bioavailability of topical drugs [10] for sites which are more difficult to access. For example, CsA four times a day has been used to treat refractory cases of blepharoconjunctivitis in children [15].…”
Section: Main Textmentioning
confidence: 99%